2014
DOI: 10.1016/j.brainresbull.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin improves sociability in the BTBR T+Itpr3/J mouse model of autism spectrum disorders

Abstract: Overactivation of the mammalian target of rapamycin (mTOR) has been implicated in the pathogenesis of syndromic forms of autism spectrum disorders (ASDs), such as tuberous sclerosis complex, neurofibromatosis 1, and fragile X syndrome. Administration of mTORC1 (mTOR complex 1) inhibitors (e.g. rapamycin) in syndromic mouse models of ASDs improved behavior, cognition, and neuropathology. However, since only a minority of ASDs are due to the effects of single genes (~10%), there is a need to explore inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…The main reason for this result might be the low rapamycin dose. In our experiment, 1 mg/kg rapamycin daily was injected to the pups, whereas 6-10 mg/kg rapamycin was usually used to in previous studies (Burket et al, 2014). Furthermore, rapamycin co-treatment ameliorates the symptoms of ASD, suggesting that suppression of mTOR signaling has important therapeutic values in VPA-exposed ASD patients.…”
Section: Discussionmentioning
confidence: 92%
“…The main reason for this result might be the low rapamycin dose. In our experiment, 1 mg/kg rapamycin daily was injected to the pups, whereas 6-10 mg/kg rapamycin was usually used to in previous studies (Burket et al, 2014). Furthermore, rapamycin co-treatment ameliorates the symptoms of ASD, suggesting that suppression of mTOR signaling has important therapeutic values in VPA-exposed ASD patients.…”
Section: Discussionmentioning
confidence: 92%
“…For example, knocking out Tsc1 in cerebellar Purkinje cells leads to increased mTOR signalling and autistic-type traits, such as abnormal social interactions, repetitive behaviours, and abnormal vocalizations -all of which could be prevented with rapamycin 84 . Similarly, rapamycin alleviated autistic-type behaviours (deficits in social preferences, abnormalities in ultrasonic vocalizations, repetitive grooming) in another mouse model of autism 85 . One recent study has also implicated mTOR in autism in humans: postmortem analysis of brain tissue from patients with autism spectrum disorders revealed increased density of dendritic spines on layer V pyramidal cells as well as aberrant mTOR activation and reduced autophagy 86 .…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%
“…Some evidence showed that rapamycin treatment protected neuron viability in stroke, parkinsonism, and early stage Alzheimer-type Tauopathy animal models 911. Strikingly, rapamycin supplement mitigated social behavioral abnormality in ASD animal model BTBR mice;12 however, the mechanism was not well revealed.…”
Section: Introductionmentioning
confidence: 99%